SELF MONITORING APPROACH TO READING AND THINGKING(S.M.A.R.T) STRATEGY FOR COMPREHENDING DESCRIPTIVE TEXTS - Rambe, Nurkhadijah; Supardi, Iwan; Husin, Syarif (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2014)
This research was aimed to answer theseproblems;(1) ifthe S.M.A.R.T strategy improves students’ ability to comprehend descriptive texts, and if so, (2) how well the S.M.A.R.T strategy improves students’ ability to comprehend descriptive texts. The data of this research was collected by using measurement technique in form of multiple choice to measure the students’ achievement. The total of test items were 20 items. The researcher employed KR21 formula to calculate the reliability of try out test, and the result was 0.718 (Substantial). The finding of this research showed that the meanof pretest ( is 65.83, and for the mean of posttset ( is 78.89, it is shown improvement. Then, is 4.936 and the is 2.030, so the is higher than (4.936 > 2.030), it mean that Ha is accepted, the S.M.A.R.T strategy improves student’s ability to comprehend descriptive texts. Keywords: S.M.A.R.T Strategy, comprehending, Descriptive Texts. Abstrak: Penelitian inibertujuan untuk menjawab masalah – masalah tersebut dibawah ini; (1) apakah strategi S.M.A.R.T meningkatkan kemampuan siswa dalam memahami teks deskriptif, dan jika iya, (2) Seberapa baik strategi S.M.A.R.T untuk meningkatan kemampuan siswa dalam memahami teks deskriptif. Data dalam penelitian ini dikumpulkan menggunakan tekhnik hitungan dalam bentuk pilihan ganda untuk mengukur pencapaian siswa.Jumlah test ada 20 soal. Peneliti mencari formula KR21 untuk menghitung reliability test, dan hasilnya adalah 0.718 (substantial). Hasil dari penelitian ini menunjukan rata – rata pretest ( adalah 65.83, dan untuk rata – rata posttest ( adalah 78.89, menunjukkan peningkatan. Selanjutnya, adalah 4.936 danadalah 2.030, jadi nilai lebih tinggi dari (4.936 > 2.030), yang berarti bahwa Ha diterima, StrategiS.M.A.R.T meningkatkan kemampuan siswa dalam memahami teks deskriptif. Kata Kunci:Strategi S.M.A.R.T, Memahami,Teks Deskriptif.